Teaching Science with Technology: A Pedagogical Hypermedia for the Science Discipline - Ajlouni, Aseel O.; Jaradat, Suhair A. (International Journal of Psychosocial Rehabilitation, 2020)
This is a research and development (R&D) study presenting the design and development of a pedagogical hypermedia environment for the science discipline (PHFSD) targeted fifth-grade students. It was developed based on a five-development model according to pedagogical hypermedia design, constructivist principles, and science curriculum. The PHFSD is intended to support fifth-grade students learn science, motivate them to learn the subject, enhance their scientific concept acquisition, and prompt their self-regulated learning skills. The PHFSD’s quality was evaluated by a panel of experts and implemented on 50 fifth grade students in a private school in Amman, the result reveled that the quality of PHFSD is very good, it is efficient for learning and teaching, and appropriate for the targeted audience.